Research Progress on Preparation and Applications of Transparent Wood/Bamboo-Based Luminescent Materials - Pillay, Cody; Langrock, Saramill; Fromm, Chanto; Jong, Brendan (Journal of Green Energy and Environmental Engineering, 2023)
Transparent wood- and bamboo-based materials are a novel type of composite material obtained by delignification of wood or bamboo followed by polymer infiltration. They not only possess high transparency and excellent mechanical properties but can also exhibit multiple functionalities such as flame retardancy, UV resistance, conductivity, and color change through appropriate functionalization. They show broad application prospects in fields like green building, flexible electronics, and photonic functional devices. In recent years, with the continuous deepening of research on sustainable functional materials, the introduction of luminescent functions into transparent wood/bamboo structures to prepare composite materials with luminescent characteristics has become a research hotspot in the field of photonic functional materials. This article systematically introduces the preparation methods of transparent wood/bamboo-based luminescent materials. Starting from luminescence mechanisms and functional material types, it elaborates on the composite strategies and typical applications of organic luminescent materials (fluorescent dyes, organic phosphors), inorganic luminescent materials (rare-earth-doped materials, semiconductor quantum dots), and organic-inorganic composite luminescent materials (perovskite materials, metal-organic frameworks) in transparent wood. Finally, it discusses key challenges faced by transparent wood/bamboo-based luminescent materials, such as stability, luminescence efficiency, and scalable preparation, and prospects their future development directions in smart construction, energy, sensing, agriculture, and other fields. The aim is to provide reference and insights for further research and application of transparent wood/bamboo-based luminescent materials.